Dynamic Visualisation of Tourism Impact in the Ningaloo Region - West, Geoffrey; Jones, Tod (WALIS, 2011)
The Ningaloo region in the northwest of Western Australia is a popular tourist destination with its primary attraction being its unique and fragile environment. While the environmental impacts of tourism are concerning, they need to be considered alongside tourism growth, since it is the largest regional economic activity. To explore impacts of tourism, complex models have been constructed that include drivers, such as fuel costs and a resources boom, and how these can affect local communities, the economy and the environment, including the number of tourists, required resident numbers, accommodation, fish stocks and jobs. Such models usually produce tables and graphs that often fail to communicate messages to a broad audience. This paper explores visualisation techniques targeted to show impact in a number of visually pleasing ways using a digital earth environment. Changes for specific sub regions for beach visitors, houses and caravans can be shown both spatially and temporally. The results of tourism models are processed on the fly as required by the user and displayed using Google Earth embedded in web pages. Techniques used include 3D models, images, icons and pop up graphs.